2017
DOI: 10.1002/adsc.201700358
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Cyclopentane‐Substituted Oxindoles via Organocatalytic Desymmetrization of Cyclopent‐4‐ene‐1,3‐diones

Abstract: The highly enantioselective desymmetrization of prochiral cyclopent‐4‐ene‐1,3‐diones has been developed via an organocatalytic Michael reaction. This desymmetrization protocol is efficiently catalyzed by 10 mol% of a bifunctional squaramide, offering a short entry into a series of cyclopentane‐substituted oxindoles bearing two quaternary and one tertiary stereocenters in good yields and high stereoselectivities.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 61 publications
0
10
0
1
Order By: Relevance
“…This thiourea-catalyzed process proceeded via cascade Michael addition/ oxidation to forge functionalized compounds (33) in 14-95% yields with 50-87% enantioselectivities. Additionally, the same group simultaneously realized an organocatalytic Michael addition reaction of 3-substituted oxindoles with cyclopentenediones in the same year [52]. Later in 2019, the Wang group observed that the application of N-methoxy amides as nucleophiles and commercially available cinchonidine as the catalyst could lead to a formal C(sp 2 )−H amidation of cyclopentenediones [53] and a practically identical case was reported by Chegondi [54].…”
Section: Desymmetrization Of Prochiral Enonesmentioning
confidence: 80%
“…This thiourea-catalyzed process proceeded via cascade Michael addition/ oxidation to forge functionalized compounds (33) in 14-95% yields with 50-87% enantioselectivities. Additionally, the same group simultaneously realized an organocatalytic Michael addition reaction of 3-substituted oxindoles with cyclopentenediones in the same year [52]. Later in 2019, the Wang group observed that the application of N-methoxy amides as nucleophiles and commercially available cinchonidine as the catalyst could lead to a formal C(sp 2 )−H amidation of cyclopentenediones [53] and a practically identical case was reported by Chegondi [54].…”
Section: Desymmetrization Of Prochiral Enonesmentioning
confidence: 80%
“…The same research group further reported an organocatalytic Michael addition of oxindoles 12 on prochiral cyclopentene‐1,3‐diones 3 via enantioselective desymmetrization (Scheme 6). [19] This reaction was efficiently catalyzed by a bifunctional squaramide C4 to yield cyclopentane‐substituted oxindoles 13 having two quaternary stereocenters with good diastero‐ and enantioselectivities (up to 97 : 3 er) in high yields (71–95% yield). To highlight the practical applicability of this protocol, substrates with electronically and sterically diverse functional groups were investigated ( 13 a – d ) and a gram scale reaction was also demonstrated with excellent yield and enantioselectivity under standard reaction conditions.…”
Section: Hydrogen Bonding Catalysismentioning
confidence: 99%
“…In the year 2017, Dieter Enders and co-workers developed an enantioselective desymmetrization protocol of prochiral cyclopentene-1,3-diones (1) through an organocatalytic approach. [32] Bifunctional squaramide [33] (C8) (10 mol%) was used as an organocatalyst in this asymmetric Michael addition. The reaction of 3-aryloxindoles (35) and substrate 1 occurred in very simple conditions with organocatalyst (C8) in DCM at room temperature within 12 h (Scheme 8).…”
Section: Desymmetrization Via Alkylation Arylation and Amidation Promentioning
confidence: 99%
“…Squaramide catalyzed Michael addition of 3-aryloxindoles to cyclopentene-1,3-diones. [32] [3 + 2] cycloaddition of prochiral cyclopentene-1,3-diones (1) with azomethine ylide (46) by using Ag(I)/TF-BiphamPhos (L14) for the synthesis of bicyclic-pyrrolidine derivatives (47) via enantioselective desymmetrization protocol under mild reaction condition (Scheme 13). [39] Synthesis of highly functionalized enantioenriched bicyclic-cyclopentane/pyrrolidine was very well explained through 1,3 dipolar cycloaddition of azomethine ylide with excellent yield and diastereoselectivity.…”
Section: Desymmetrization Via Cycloaddition Reactionmentioning
confidence: 99%
See 1 more Smart Citation